Oral Cancer Current Concepts and Future Perspectives - Sridharan, Gokul (IntechOpen, 2022)
Oral cancer is a common disease with a high incidence of morbidity and mortality. Despite technological advancements in diagnosis and treatment, the five-year survival rate is low. Researchers worldwide are attempting to identify new and novel methods for early diagnosis and better treatment of oral cancer to improve survival rate and quality of life post recovery. This book examines current concepts in oral cancer and emphasizes future perspectives for diagnosis and treatment of disease for better clinical outcomes and patient care.